1997
DOI: 10.1111/j.1440-1797.1997.tb00288.x
|View full text |Cite
|
Sign up to set email alerts
|

A clinicopathological study of adult Japanese IgA nephropathy patients: Early stage cases and cases with exacerbation

Abstract: Most cases of adult type IgA nephropathy (IgAN) have an insidious onset and asymptomatic course. However, some patients reveal recurrent macroscopic haematuria following episodes of respiratory or urinary tract infections. In order to clarify the correlation between clinical features and histological alterations or prognosis, 42 cases of early stage IgAN and 40 cases with acute exacerbation episodes were investigated and compared with a control group. Early stage cases were defined as having had a renal biopsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The results of the present study are in accordance with those of the previous studies in showing that females had milder pathologic changes whereas males were shown to have more aggressive forms 17. A difference in the incidence of macroscopic hematuria in adult patients was found when compared between various geographical regions 18. In European countries, the reported incidence exceeded 50%;1920 whereas in Japan, the incidence ranged from 15% to 31% 2122.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The results of the present study are in accordance with those of the previous studies in showing that females had milder pathologic changes whereas males were shown to have more aggressive forms 17. A difference in the incidence of macroscopic hematuria in adult patients was found when compared between various geographical regions 18. In European countries, the reported incidence exceeded 50%;1920 whereas in Japan, the incidence ranged from 15% to 31% 2122.…”
Section: Discussionmentioning
confidence: 93%
“…17 A difference in the incidence of macroscopic hematuria in adult patients was found when compared between various geographical regions. 18 In European countries, the reported incidence exceeded 50%; 19 20 whereas in Japan, the incidence ranged from 15% to 31%. 21 22 This difference in distribution can be attributed to the difference in the nature of the disease, which could be linked to genetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…9 The percentage of interstitium exhibiting damage (cell infiltration, fibrotic change, or amyloid deposit) was also assessed, according to the method reported by Shimada et al 10 The percentage of sclerosed glomeruli was also determined.…”
Section: Methodsmentioning
confidence: 99%